Control Strategy to Generate PWM Signals with Stability Analysis for Dual Input Power Converter System - JN Hemalatha; SA Hariprasad; GS Anitha (IAES Indonesian Section, 2019)
The prime role of a renewable resource based DC hybrid power system is, to maintain the output voltage constant with higher efficiency. In order to achieve this the duty cycles of the converter switches are dynamically controlled. Multiple input single output (MISO) converter uses separate controller for adjusting the duty cycle, this complicates the design and implementation of the system. Hence, to overcome this limitation a centralized controller is used. The control strategy depends on the pattern of gating signals given to the converter switches. When independent controller is employed, then gating signals of any pattern can be used to drive the switches. However, if a single controller is used, and then a definite pattern is very much essential otherwise, the output voltage and efficiency gets affected. In this paper, an attempt is made to validate and evaluate the performance parameters of MISO converter with two pattern of gating signals; they are synchronized and unsynchronized pulses at their rising edge. The control strategy focusses on the generation of these gating pulses. PID controller is tuned appropriately to determine the gains to achieve the stability of the proposed converter. The dual input power converter validated to show how the PWM pattern affects the efficiency, ripple and regulation of the converter. Using MATLAB SIMULINK platform the simulation of the proposed concept with dual input converter in closed loop is validated. Simulation results proves that synchronized pulses gives DC efficiency of 87% at designed output of 12V output. Converter with unsynchronized PWM pulses operates at lesser efficiency of 75% and the output voltage is of 10V.